Amidoalkylindoles as Potent and Selective Cannabinoid Type 2 Receptor Agonists with in Vivo Efficacy in a Mouse Model of Multiple Sclerosis - Shi, Y.; Duan, Y.; Ji, Y.; Wang, Z.; Wu, Y.; Gunosewoyo, Hendra; Xie, X.; Chen, J.; Yang, F.; Li, J.; Tang, J.; Xie, X.; et al. (American Chemical Society, 2017)
Selective CB 2 agonists represent an attractive therapeutic strategy for the treatment of a variety of diseases without psychiatric side effects mediated by the CB 1 receptor. We carried out a rational optimization of a black market designer drug SDB-001 that led to the identification of potent and selective CB 2 agonists. A 7-methoxy or 7-methylthio substitution at the 3-amidoalkylindoles resulted in potent CB 2 antagonists (27 or 28, IC 50 = 16-28 nM). Replacement of the amidoalkyls from 3-position to the 2-position of the indole ring dramatically increased the agonist selectivity on the CB 2 over CB 1 receptor. Particularly, compound 57 displayed a potent agonist activity on the CB 2 receptor (EC 50 = 114-142 nM) without observable agonist or antagonist activity on the CB 1 receptor. Furthermore, 57 significantly alleviated the clinical symptoms and protected the murine central nervous system from immune damage in an experimental autoimmune encephalomyelitis (EAE) mouse model of multiple sclerosis.